Percentage of Broiler Giblets Fed With Flour Rations by-Products of Chicory (Brassica pekinensis L) - Alfiah Mahya; Muhammad Amrullah Pagala; Nur Santy Asminaya; Fuji Astuty Auza; Deki Zulkarnain (Indonesian Journal Of Animal Agricultural Science (IJAAS), 2023)
Gerbage chicory is a by-product or the result of weeding most vegetable parts and is easily found in traditional markets but cannot be consumed by humans anymore. This study aimed to analyze the effect of flour of chicory by-products on the percentage of giblet (gizzard, liver, and heart) of broiler chickens. This study used a completely randomized design (CRD) consisting of 4 treatments and 5 replications. In each treatment replication, there were 5 broiler chickens. The treatments used were: P0 = ration without flour of chicory by-products, P1 = ration with 5% flour of chicory by-products, P2 = ration with 10% flour of chicory by-products, and P3 = ration with 15% flour of chicory by-products. The results showed that the average weight of the gizzard, liver, and heart was 2.54-3.11%, 2.86-3.41%, and 0.64-0.71%, respectively. The provision of flour of chicory by-products did not significantly affect the percentage of heart. However, it had a significant effect (P<0.05) on the percentage of liver and gizzard. The percentage of broiler liver increased with the treatment level, and the percentage of gizzard increased at the level of treatment of 5% and 10% flour of chicory by-products. It can be concluded that the addition of flour from chicory by-products to broilers is still safe and does not interfere with the performance of giblets up to a level of 15%